Development of Students’ Worksheets for Fiqh Learning Based on the Implementation of the Independent Curriculum at the Elementary Madrasah Level - Andi Darwati; Muhammad Asra; Muh. Iqbal (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to develop Student Worksheets (LKPD) for Fiqh learning based on the implementation of the Merdeka Curriculum at the Madrasah Ibtidaiyah level and to analyze the validity, practicality, and effectiveness of these worksheets in the learning process. This study employs the Research and Development (R&D) method, using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The study was conducted at MIN 1 Kolaka and MIS Nurul Iman Pomalaa with research subjects of grade IV students. The research instruments used included expert validation sheets, observation sheets for learning implementation, student response questionnaires, and learning outcome tests. The results showed that the developed Student Worksheets for Fiqh learning obtained an average validity value of 3.57, categorized as very valid. The level of practicality based on the results of observations of learning implementation obtained an average value of 1.74, categorized as fully implemented. Meanwhile, the product's effectiveness was demonstrated by improved student learning outcomes, with an average N-Gain score of 0.78 at MIN 1 Kolaka and 0.77 at MIS Nurul Iman Pomalaa, both in the high category. Therefore, the developed Student Worksheets for Fiqh learning based on the implementation of the Independent Curriculum are declared valid, practical, and effective for use in Fiqh learning at Islamic Elementary Schools (Madrasah Ibtidaiyah).